Asian “Guan” Parenting and Life Satisfaction Among Adolescents in Malaysia: The Mediating Role of Filial Piety - Nainee, Sarvarubini; Tan, Soon-Aun; Tan, Chee-Seng; Gan, Su-Wan; Tan, Jo-Pei (Frontiers in Psychology, 2021)
Literature on adolescent development has shown that parenting practices have positive relationships with adolescents’ life satisfaction. Adolescents’ life satisfaction improves when they have parents low in psychological control who uphold reciprocal self-disclosure in their communication. Guan parenting was found to correlate positively with adolescents’ development. Therefore, it is methodologically important to replicate the investigation on the relationship between adolescents’ life satisfaction and Guan parenting. Literature suggests that filial piety is shaped by parenting practices and adolescents who perceived intense parental concern, care, and involvement tend to uphold filial piety and express gratitude toward parents which may promote the adolescents’ life satisfaction. In this study, mediation analysis was done to elucidate the relationship among parents’ guan parenting style, filial piety, and life satisfaction on 606 adolescents (Mage=15.07; SDage=1.03; 52.1% females) in Malaysia. The adolescents were sampled through cluster sampling and data was collected using self-administered questionnaires. The results showed positive relationship between paternal and maternal guan parenting with filial piety and adolescents’ life satisfaction. Greater parents’ filial piety was linked to higher life satisfaction among adolescents. Findings from the mediation models indicated the association among guan parenting with filial piety, gratitude towards parents, and higher life satisfaction. The findings also offered empirical evidence to the underlying mechanism of how guan parenting could affect adolescent life satisfaction via the mediating role of filial piety. The findings also supported the importance of culture-infused parenting in inculcating adolescents’ filial piety besides establishing its link to life satisfaction in Asian families.